2004
DOI: 10.1590/s1415-47572004000200026
|View full text |Cite
|
Sign up to set email alerts
|

Several pathways of hydrogen peroxide action that damage the E. coli genome

Abstract: Hydrogen peroxide is an important reactive oxygen species (ROS) that arises either during the aerobic respiration process or as a by-product of water radiolysis after exposure to ionizing radiation. The reaction of hydrogen peroxide with transition metals imposes on cells an oxidative stress condition that can result in damage to cell components such as proteins, lipids and principally to DNA, leading to mutagenesis and cell death. Escherichia coli cells are able to deal with these adverse events via DNA repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 126 publications
(128 reference statements)
1
42
0
Order By: Relevance
“…[1,2] Before pequioil supplementation, results suggested that the tolerance for an increased oxidative stress and consequent DNA damage happened only with H 2 O 2 at up to 0.25 mM; the treatment with H 2 O 2 at 1 mM increased oxidative stress above the capacity of the organism to adapt. However, this tolerance did not occur for age group above 41 years, distances above 10 Km and the genotypes MnSOD Ala/Ala, CAT TT and ACE ID.…”
Section: Wwwantioxorg Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Before pequioil supplementation, results suggested that the tolerance for an increased oxidative stress and consequent DNA damage happened only with H 2 O 2 at up to 0.25 mM; the treatment with H 2 O 2 at 1 mM increased oxidative stress above the capacity of the organism to adapt. However, this tolerance did not occur for age group above 41 years, distances above 10 Km and the genotypes MnSOD Ala/Ala, CAT TT and ACE ID.…”
Section: Wwwantioxorg Discussionmentioning
confidence: 99%
“…[1] If not controlled, the reaction of H 2 O 2 with transition metals can provoke oxidative stress in the under Increased Hydrogen Peroxide conditions, the Antioxidant Effects of Pequi oil (Caryocar brasiliense camb.) to decrease dnA damage in runners are Influenced by Sex, Age and oxidative Stress-related Genetic Polymorphisms www.antiox.org of ROS, deficient antioxidant defenses, or a combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, radioadaptive response induction expresses the ability of low dose radiation to induce cellular changes that alter the level of subsequent radiation-induced or spontaneous damage (Amundson et al, 1999). The exposure to minimal stress inducing a very low level of damage can trigger an AR resulting in increased resistance to higher levels of the same or of other types of stress (Patra et al, 2003;Asad et al, 2004;Girigoswami & Ghosh, 2005;Yan et al, 2006). The AR could be considered a nonspecific phenomenon and have been confirmed but not explained by many studies.…”
Section: Hormesis and Molecular Mechanisms Of The Adaptive Responsementioning
confidence: 99%
“…Thus, radioadaptive response induction expresses the ability of low dose radiation to induce cellular changes that alter the level of subsequent radiation-induced or spontaneous damage. The AR could be considered a nonspecific phenomenon -the exposure to minimal stress inducing a very low level of damage can trigger an AR resulting in increased resistance to higher levels of the same or of other types of stress (Joiner et al, 1996;Wolff, 1998;Joiner et al, 1999;Patra et al, 2003;Asad et al, 2004;Girigoswami and Ghosh, 2005;Yan et al, 2006). The AR has been observed in many different organisms: bacteria, yeast, the algae Oedogonium cardiacam, Chlamydomonas reinhardtii, Closterium monoliferum and Chlorella pyrenoidosa, in higher plants, insect cells, mammalian cells, human cells in vitro, and in animal models in vivo during a protracted (low dose-rate) exposure prior to an acute dose treatment Laszlo, 1971, 1973;Bryant, 1974Bryant, , 1975Bryant, , 1976Bryant, , 1979Cowie, 1976, 1978;Olivieri et al, 1984;Santier et al, 1985;Wolff et al, 1988;Boreham and Mitchel, 1991;Rieger et al, 1993;Mahmood et al, 1996;Salone et al, 1996;Panda et al, 1997;Asad et al, 1997Asad et al, , 1998Wolff, 1998;Nikolova et al,showing gene expression changes, DNA single-and double-strand breaks, biochemical analyses of enzymatic and/or non-enzymatic antioxidant defence system (Hillova and Drasil 1967;Bryant, 1975Bryant, , 1976Bryant, , 1979Rieger et al, 1993;Ikushima et al, 1996;Rigaud and Moustacchi, 1996;Panda et al, 1997;…”
Section: The Adaptive Responsementioning
confidence: 99%